Minority languages and cultural diversity in Europe : Gaelic and Sorbian perspectives - Glaser, Konstanze, 1968- (Linguistic diversity and language rights ;, 2007)
Combines a theoretical understanding of minority languages and associated language rights, alongside an examination of two particular European minority language communities. This book explores contemporary ethnocultural minority agendas in Europe, and covers key aspects of Europe's least explored "linguistic cultures" such as Gaelic and Sorbian.